2004
DOI: 10.1103/physreva.69.049905
|View full text |Cite
|
Sign up to set email alerts
|

Publisher's Note: Pulse-train nonuniformity in a fiber soliton ring laser mode-locked by using the nonlinear polarization rotation technique [Phys. Rev. A69, 043808 (2004)]

Abstract: Publisher's Note: Pulse-train nonuniformity in a fiber soliton ring laser mode-locked by using the nonlinear polarization rotation technique [Phys. Rev. A 69, 043808 (2004)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…We have developed a numerical technique to accurately simulate the soliton dynamics in the lasers. We have shown previously that with the technique we could precisely reproduce the soliton properties such as the soliton sideband asymmetry [7], soliton subsideband generation [8], bound states of solitons [9] and soliton pulse nonuniformity [5]. In addition, in the case of small soliton pulse variation, our simulations merged to those obtained from the GLE.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…We have developed a numerical technique to accurately simulate the soliton dynamics in the lasers. We have shown previously that with the technique we could precisely reproduce the soliton properties such as the soliton sideband asymmetry [7], soliton subsideband generation [8], bound states of solitons [9] and soliton pulse nonuniformity [5]. In addition, in the case of small soliton pulse variation, our simulations merged to those obtained from the GLE.…”
supporting
confidence: 58%
“…Therefore, the lasers offered themselves as an ideal experimental test bed to investigate the dissipative soliton dynamics. Current experimental studies on the soliton dynamics in the lasers have also revealed a number of new interesting phenomena; these include the bound states of solitons [3,4], soliton energy nonuniformity [5], and period-doubling bifurcations and route to chaos [6]. As those phenomena were experimentally obtained either under the strong direct soliton interaction or soliton pulses experienced significant energy variation within one cavity round trip, the conventional GLE can no longer describe their dynamics.…”
mentioning
confidence: 99%
“…Although in a fiber ring laser the dispersive waves periodically experience gain provided by the erbium-doped fiber and loss at the output coupler which lead to periodic power fluctuation, this kind of power variation is too small and the modulation instability with subsideband generation can not be observed in the experiment [15]. Nevertheless, when the strength of dispersive waves is strong enough, a larger periodic power variation of dispersive waves induced by the interaction between intensity-dependent polarization rotation and passive polarizer [16][17][18][19] can be realized by properly setting the linear cavity phase delay. In this paper, we present the experimental observation of modulation instability induced by periodic power variation in a passively mode-locked fiber ring laser.…”
Section: Introductionmentioning
confidence: 99%
“…Bifurcation is a universal dynamic of nonlinear systems, which has been observed in physics, biology, chemistry, and even economics . In laser systems, period-doubling bifurcation has been widely observed in semiconductor lasers, mode-locked solid-state lasers, mode-locked fiber lasers, and so forth. For the period-doubling state of mode-locked lasers, the output pulse train is not uniform and alters periodically.…”
Section: Introductionmentioning
confidence: 99%